Fire resistance of reinforced concrete columns - Yao, Yao. (2008)
This study aims to develop a simple and unified analytical method for predicting fire resistance of reinforced concrete (RC) columns under fire conditions. The effects of elevated temperatures on material deterioration, and thus strength and stability of columns, are assessed. This leads to a straightforward and rational method – the ACT method.